Productivity, profitability and energetics of direct seeded rice under different nutrient and tillage management practices: Nutrient and tillage management in direct seeded rice - Swain, Pratikshya; Jena, Jagadish; Sahoo, Sai Abinash; Behera, Stuti Debapriya; Dash, Subhaprada; Behera, Prakash Ranjan; Behera, Basudev (ORYZA-An International Journal of Rice, 2026)
A field experiment was conducted during the kharif season of 2024 at the Agricultural Research Station, SOA University, Bhubaneswar, Odisha, to evaluate the effect of nutrient management practices under different tillage systems on the productivity and profitability of direct-seeded rice (DSR). The experiment was laid out in a split-plot design with three tillage practices in the main plots: conventional tillage, minimum tillage with dhaincha brown manuring at 50% seed rate, and minimum tillage with dhaincha brown manuring at 100% seed rate. Four nutrient management options, namely control, inorganic recommended dose of nitrogen (RDN) @ 60 kg ha-1,organic nutrient management, and integrated nutrient management (INM; 25% organic + 75% inorganic), were assigned to the subplots and replicated thrice. Results revealed that minimum tillage with dhaincha brown manuring at 100% seed rate significantly improved growth and yield attributes, resulting in the highest grain yield (2194 kg ha-1) and straw yield (2761 kg ha-1). Among nutrient management practices, INM recorded the maximum tiller density (263.7 m-2), grain yield (2280 kg ha-1), and straw yield (2780 kg ha-1). Economic analysis indicated that minimum tillage with dhaincha brown manuring at 100% seed rate generated the highest net return (Rs.16,750 ha-1) and benefit-cost ratio (1.45), whereas inorganic RDN exhibited the highest economic efficiency (Rs.192.6 ha-1 day-1). The study suggests that integrating minimum tillage with dhaincha brown manuring at 100% seed rate and INM can enhance productivity, profitability, and sustainability of direct-seeded rice cultivation.